ANALISIS RENCANA PELAKSANAAN PEMBELAJARAN TEMATIK DI KELAS V SEKOLAH DASAR LKIA PONTIANAK SELATAN - Hariati Hariati; Tahmid Sabri; Kartono Kartono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis observation aims to analyze the implementation plan of thematic learning at theLKIA Pontianak Elementary School. Specifically, this study aims to describe thecompleteness and suitability of the components contained in the learning device plan. Themethod used in this research was descriptive qualitative. The results showed that thelesson plans used at SD LKIA Pontianak had met the existing standards. The thingillustrated that the RPP design had fulfilled all the components that should have beenincluded in the RPP based on Permendikbud No. 22 of 2016. The suitability of thecomponents in the RPP for thematic subjects at SD LKIA Pontianak are generallyappropriate but there are several weaknesses, including the use of the operational degreeverb in the learning objectives that are not applied to every point in the learningobjectives, material design and learning media that did not optimize the output oftechnology, the design of learning strategies that do not maximize the elements ofinnovation and creativity of students, as well as the design of learning objectives andevaluations that do not implement HOTS, while the other components contained in theRPP assessment rubric have been fulfilled or appropriate.Keyword : Lesson Plan, Thematic Learning, Learning Lesson Plan Components